Behavioral Intention of Dairy Farmers of Punjab State of India towards Antimicrobial Usage: A Dairy Perspective Study - Patnaik, Neela Madhav; Gupta, Jancy; Kar, Priyajoy; Acharya, Parag; Das, Arghyadeep; Gupta, Jagdeep (International Journal of Livestock Research, 2019)
Antimicrobial resistance is a multi-sectoral global threat affecting human and animal health as well as environment. For ensuring prudent use of antimicrobials as a disease control measure on dairy farms, research is needed to understand farmers psychological factors that influence decision-making empirically. The present study looks into the capabilities and facilitating factors of dairy farmers for usage of antimicrobials drugs and their attitude towards its use. The study was conducted in Punjab state of Northern India which was purposively selected and data were collected by structured interview schedule from 180 dairy farmers. The study revealed that cost incurred in purchase of antimicrobials and reduction of antimicrobial use through better management practices to enhance the profit ranked first for outcome attitude. Social referents veterinary doctor and scientist were ranked first and second respectively and were considered credible information sources by the dairy farmer for animal health management practices. Purchasing the full recommended dose and the relative easiness/difficulty associated with purchasing it was ranked first for perceived behavioural control items. To ensure rational usage of antimicrobials without affecting access to antimicrobials, spreading awareness among farmers and increasing the communication among the professionals and field functionaries is a crucial step.